AC Humidity Sensing Properties of Mesoporous K2CO3-SiO2 Composite Materials - Liang Guo; Xuefeng Chu; Xiaohong Gao; Chao Wang; Yaodan Chi; Xiaotian Yang (Journal of Chemistry)
The mesoporous silica SBA-15 and mesoporous K2CO3-SiO2 composite material were synthesized. Characterization of microstructure and morphology of materials indicated that the composite material had saved the porous framework of mesoporous silica SBA-15. Humidity sensing properties of different inverse proportion K2CO3-SiO2 composite material were studied and we found that the sample with 0.16 g/g K2CO3 exhibited excellent linearity in the wide humidity range. The complex impedance changed five orders of magnitude from 11% RH to 95% RH. The rapid response and recovery time were 10 s and 38 s, respectively. Finally a feasible ion transfer mechanism was brought forward to explain the sensing mechanism.